Morphological Characterization of 160 Accessions of Sesame (Sesamum indicum L.) from the Colombian Germplasm Bank - Garnica Montaña, Johanna Paola; Rodríguez- Rodríguez, Óscar Jair; Jaramillo-Barrios, Camilo Ignacio; Villamil Carvajal, Jorge Enrique; Valencia Montoya, Jorge Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Sesame seed is an important plant in the production of high-quality edible oil for its high nutritional and therapeutic value. The characterization of accessions is necessary for the identification of parents with characteristics of interest for obtaining new genetic materials. 160 accessions of sesame (Sesamum indicum L.) were characterized in the Nataima, municipality of El Espinal (Tolima), managed by the National Germplasm Banks System for Food and Agriculture, of which, 136 are from 25 countries; 81 descriptors were used, 30 quantitative and 51 qualitative. Factor analysis of mixed data was performed, and homogeneous groups were generated by cluster analysis for five groups of variables: plant and seedling, stem and root, leaf, seed and capsule and flower. 25 discriminating variables were selected from the previous structures and a new cluster analysis was performed. This generated five main groupings influenced by qualitative variables: habit, type of growth and height in plant and seedling; type of branching, pubescence and number of primary branches in stem and root; position, petiole length and leaf width; position of the capsule, color of the cover and number of capsules in seed and capsule and coloration of the corolla, extrafloral nectary and number of flowers per armpit in flower. The accessions TEHUANTEPEC SELEC, L-AJ-M-67, L-AJ-M-51, BROWN HAIR, CREOLE WHITE, NP-61, BACCHUS, INSTITUTE 104, RED CHINESE, R 198 and ACARIGUA present characteristics of interest that differentiate the formed groups. The discriminant variables and the identified materials allow the generation of varieties for future breeding programs in Colombia.